Assessing readiness for independent self-care in adolescents with type 1 diabetes: Introducing the RISQ. (April 2020) - Goethals, Eveline R.; Commissariat, Persis V.; Volkening, Lisa K.; Markowitz, Jessica T.; Laffel, Lori M.
Abstract: Aim: To design and evaluate psychometrics of adolescent self-report and parent proxy-report questionnaires assessing readiness for independent self-care in adolescents with type 1 diabetes (RISQ-T and RISQ-P). Methods: 178 adolescents with type 1 diabetes (ages 13–17 years) and their parents completed the 20-item RISQ-T and 15-item RISQ-P, along with diabetes-specific measures of parent involvement, self-efficacy, burden, and treatment adherence. Evaluation of psychometric properties included calculation of internal consistency, adolescent and parent agreement, test-retest reliability, concurrent and predictive validity. Results: The RISQ-T (α = 0.78) and RISQ-P (α = 0.77) demonstrated sound internal consistency. Higher RISQ-T and RISQ-P scores (indicating more adolescent readiness for independent self-care) showed significant associations with less parent involvement in diabetes care (adolescent r = −0.34; parent r = −0.47; p < .0001), greater adolescent diabetes self-efficacy (adolescent r = 0.32; parent r = 0.54; p < .0001), less parent-endorsed diabetes-related burden (parent r = −0.30; p < .0001), and greater treatment adherence (adolescent r = 0.26, p = .0004; parent r = 0.31, p < .0001). Adolescent and parent scores were significantly correlated ( r = 0.35; p < .0001); test-retest reliability was reasonable (ICC RISQ-T r = 0.66; RISQ-P r = 0.71). Higher baseline RISQ-P scores significantly predicted reduced family involvement after six months ( β = −0.14, p = .02). Conclusions: RISQ-T and RISQ-P demonstrate sound psychometric properties. Surveys may help inform diabetes teams of the level of support needed to facilitate shift to independent self-management.